The glass mountain : and other Arabian tales - Larson, Jean Russell (Philadelphia : MacRae Smith Company, 1971)
Seven traditional tales from the Middle East include'Ali and the Griffin,''Zeki the Witless,' and'King Ping.'
Keywords: Arabs -- Folklore; Tales -- Arab countries